Kazakhstan Economic Update, Fall 2015 : Adjusting to Lower Oil Prices--Challenging Times Ahead - World Bank Group (World Bank, Washington, DC, 2015)
Kazakhstan’s economy faces the challenge of adjusting to a large terms-of-trade shock in a context of declining domestic and external demand. The authorities responded to the collapse of global oil prices through a rapid fiscal adjustment followed by corresponding monetary and exchange-rate policy adjustments. A difficult external environment will continue to affect Kazakhstan’s medium-term outlook. In the medium term, the economy continues to face significant downside risks, including the possibility of delays in Kashagan offshore oil production or a protracted recession in Russia and a further slowdown in China. Over the longer term, diversification of the economy will be required to increase its resilience to external shocks.